Advances in alginate biosynthesis: regulation and production in Azotobacter vinelandii - Ponce, Belén; Zamora-Quiroz, Agustín; González, Ernesto; Andler, Rodrigo; Díaz-Barrera, Alvaro (Frontiers in Bioengineering and Biotechnology, 2025)
Alginates are polysaccharides composed of (1–4)-β-D-mannuronic acid (M) and α-L-guluronic acid (G), whose proportions influence their rheological properties and a wide range of applications in the food, pharmaceutical, and biomedical industries. Azotobacter vinelandii, a Gram-negative bacterium, has been studied for its ability to produce alginate due to its capacity to fix atmospheric nitrogen and its high respiratory activity. The biosynthesis of alginate in Azotobacter vinelandii involves precursor synthesis, polymerization, modification, and secretion, which are regulated by complex mechanisms, including the secondary messenger c-di-GMP. This regulatory network links cellular respiration with alginate yield and molecular characteristics. Fermentation strategies show that high oxygen transfer rates (OTRs) enhance alginate production, whereas low OTRs favor the synthesis of alginate with higher molecular weights and higher G/M ratios, which are crucial for advanced applications such as hydrogels and drug delivery systems. Insights into these biosynthetic and regulatory processes enable scalable production of high-quality alginate, bridging laboratory research with industrial applications and expanding its potential in the biotechnological and medical fields.